Energy-Efficient, Utility Accrual Real-Time Scheduling Under the Unimodal Arbitrary Arrival Model - Wu, Haisang; Ravindran, Binoy; Jensen, E. Douglas (Design, Automation and Test in Europe, 2005)
We present an energy-efficient real-time scheduling algorithm called EUA*, for the unimodal arbitrary arrival model (or UAM). UAM embodies a "stronger" adversary than most arrival models. The algorithm considers application activities that are subject to time/utility function time constraints, UAM, and the multi-criteria scheduling objective of probabilistically satisfying utility lower bounds, and maximizing system-level energy efficiency. Since the scheduling problem is intractable, EUA* allocates CPU cycles, scales clock frequency, and heuristically computes schedules using statistical estimates of cycle demands, in polynomial-time. We establish that EUA* achieves optimal timeliness during under-loads, and identify the conditions under which timeliness assurances hold. Our simulation experiments illustrate EUA*'s superiority.